Pengaruh Harga, Promosi Dan Kualitas Layananterhadap Kepuasan Pelanggan Gojek (Go-Ride) Pada Mahasiswa Fakultas Hukum UNPRI - Sherla Wijaya; Winda Sri Astuti Doloksaribu; Yunus Andreas Sianturi; Chelsea Rajagukguk; Anjarani Anjarani; Erwina Erwina (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The Influence Of Price, Promotion And Service Quality On Gojek (Go-Ride) Customer Satisfaction In Students Of The Faculty Of Law UNPRI. Faculty of Economics, Prima Indonesia University. Thesis. This study aims to determine the effect of price on Gojek (Go-Ride) customer satisfaction, determine the effect of promotion on Gojek (Go-Ride) customer satisfaction, determine the effect of service quality on Gojek (Go-Ride) customer satisfaction, and determine price, promotion and service quality simultaneously influences Gojek (Go-Ride) customer satisfaction for UNPRI Law Faculty Students. This type of research uses descriptive quantitative methods. The population in this study amounted to 364 people with a sample of 78 respondents. The data analysis used in this study is Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Test, and Coefficient ofDetermination Test (R2). The results of this study are price has a positive and significant effect on customer satisfaction, promotion has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction and price, promotion and service quality simultaneously have a positive and significant effect on customer satisfaction customer satisfaction GOJEK (Go-Ride) to UNPRI Law Faculty Students. Keywords: Price, Promotion, Service Quality, Customer Satisfaction